In vivo effects of Maillard reaction products derived from biscuits - Patrignani, Mariela (2015)
The antioxidant activity, antihypertensive effect and prebiotic activity of Maillard reaction products (MRPs) derived from biscuits were investigated in Wistar rats. Animals were fed the following diets for 6 weeks: control (AIN-93 diet); Asc-diet (AIN-93 diet with ascorbic acid in the drinking water); HT-B diet (containing high amount of MRP derived from biscuits) and LT-B diet (containing negligible amounts of biscuit MRP). Serum antioxidant activity (FRAP, ABTS), as well as lipid peroxidation (TBARS) were determined at the end of the experiment. Results showed that dietary MRP reduced the food efficiency, increased the antioxidant activity of serum, increased the ratio between lactic and total aerobic bacteria, increased water-holding capacity of faeces and reduced blood pressure, but did not reduce mineral absorption. Therefore, the biscuit MRP functional claims could be demonstrated by an in vivo study.